2020
DOI: 10.3390/jcm9113736
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinology Education of Nurses and the Current Immunoprophylaxis Recommendations for Children with Juvenile Idiopathic Arthritis

Abstract: Introduction: The immunosuppressive effect of the disease and the applied treatment in children with juvenile idiopathic arthritis increases the risk of infections. It is therefore essential that vaccinations be properly implemented and that a proper serological response is provoked after the vaccination. A competent nurse acting in compliance with the current recommendations constitutes one of the safety pillars of immunization of pediatric patients with juvenile idiopathic arthritis. Aim: To discuss evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…We suppose that a realistic time interval for antibody assessment in a cost-effective manner is 3 years. It is necessary to provide simple algorithms to primary care physicians regarding the management of vaccinations and routine checking of antibodies [ 36 , 39 ]. Our study’s results found that the data related to vaccination safety and efficacy strongly support the need for missed vaccinations, especially the MMR booster.…”
Section: Discussionmentioning
confidence: 99%
“…We suppose that a realistic time interval for antibody assessment in a cost-effective manner is 3 years. It is necessary to provide simple algorithms to primary care physicians regarding the management of vaccinations and routine checking of antibodies [ 36 , 39 ]. Our study’s results found that the data related to vaccination safety and efficacy strongly support the need for missed vaccinations, especially the MMR booster.…”
Section: Discussionmentioning
confidence: 99%
“…This new principle has been given a prominent place within the recommendation. Optimal vaccination of pedAIIRD patients cannot be guaranteed when it is unclear who is responsible, as is shown by the low vaccination rate in pedAIIRD patients 21 22. As the treating physician or nurse specialists have extensive expertise on the entire disease spectrum and its treatment, the committee considers it crucial that the treating physician is in charge.…”
Section: Resultsmentioning
confidence: 99%